Family Profiles of Expressed Emotion in Adolescent Patients With Anorexia Nervosa and Their Parents. Issue 3 (4th May 2017) - Rienecke, Renee D.; Lebow, Jocelyn; Lock, James; Le Grange, Daniel
Abstract : The current study examined expressed emotion (EE) among families of adolescents with anorexia nervosa (AN) participating in a treatment study. EE ratings were made from 110 adolescents toward their parents and from parents toward their children using videotaped family interviews. Participants were 92% female and 75% Caucasian with a mean age of 14.41 years. Four family profiles were created (low patient EE/low parent EE, high patient EE/high parent EE, low patient EE/high parent EE, high patient EE/low parent EE). Family EE profile was not related to full remission at end of treatment. Groups were then combined according to EE level of parent. The low parent group (defined as low on criticism, hostility, and emotional overinvolvement) had significantly lower scores on a measure of eating disorder psychopathology than the high parent group at the end of treatment. Patients with AN in low EE families do better in treatment than those patients belonging to high EE families. These findings are true regardless of the EE status of the patient.